(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1991)
The problem of the rail ways stability exists for a long time and there are about 100 theoretical methods to solve it. In this paper the connection between differential and difference methods is discussed.